Prevention of primary stroke in adults and children - T. L. Vizilo; T. V. Poponnikova; I. F. Fedoseeva (Лечащий Врач)
Modern views of stroke prevention are discussed. Universally recognized strategies of stroke prevention are analyzed and new approaches to preventive treatment of cerebral circulation disorders are proposed.